Detection of Financial Statement Fraud in Mining Companies on the Indonesia Stock Exchange - Kurniawan, Widiar Onny; Saidon, Intan Marzita; Afkar, Taudlikhul; Ferara, Wanudya Ajeng (GREENOMIKA, 2025)
Financial statement fraud is a serious threat to investor confidence and capital market stability. This study aims to determine indications of financial statement manipulation in mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) using the Beneish M-Score model. This study uses a quantitative approach with secondary data from the company's financial statements during the 2020-2023 period. A total of 15 companies were sampled based on certain criteria. The results of the analysis show that around 47% of the sample companies have an M-Score value above the -2.22 threshold, which means they have the potential to manipulate financial statements. This finding supports the fraud triangle theory and emphasizes the importance of a stronger supervisory system, especially in industries prone to external pressures such as mining. This research is expected to provide an initial overview for inventors, auditors, and regulators in assessing financial risk and as a reference in strengthening corporate governance.